Pandemic Isolation in Belarus through the Perspective of Photographs: The Case of a Family’s Quarantine - Zhuk, Krystsina (Lidé města, 2022)
This photo essay examines the process of isolation during the first period of the COVID-19 pandemic based on the quarantine photos of a family from Belarus. It illustrates how the content and form of the collected images visualized the invisible markers of the pandemic and reflected various stages of isolation, transformations of the notion of home, and changes in family dynamics and routines. To collect the photographs, a weeklong remote participatory project was conducted. The findings of this project thus pointed to a direct correlation between photographs and changes in the social world and individuals’ lives brought about by the coronavirus outbreak.